Optimization of Real-Time PCR Conditions for COVID-19 Diagnosis with Logix Smart Reagent™ - Anisa Febriyanti; Seprianto Seprianto; Titta Novianti; Febriana Dwi Wahyuni; Oktaviani Naulita Turnip; Roselein Putri; Henny Saraswati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Corona Virus Disease 2019 or COVID-19 is a new type of virus that attacks the respiratory tract and can cause death. Laboratory examinations play an essential role in diagnosing COVID-19 with a set of reagents or kits. Sampiand sampling is carried out with a nasopharyngeal swab or oropharyngeal swab. Positive samples of COVID-19 patients used in this study were converted into RNA at the COVID-19 Referral Clinic in Bekasi, after which volume optimization was carried out with a total volume of 5 µl, 8 µl, and 10 µl with the Logix Smart™ kit. The method in this study uses One-Step Real-time PCR. This method is the best method for carrying out several bear tests because it can reduce the possibility of sample contamination. The procedure is fast and has high sensitivity. The fluorescence detection used in this study was FAM with a specific target of COVID-19 RNA and ROX with a particular DNA target of RNase-P. This research was conducted to obtain optimal volume conditions under the manufacturer's standards in detecting the SARS-CoV-2 virus. The results of this study indicate that a total volume of 5 l is the optimal total volume for detecting the presence of the SARS- CoV-2 virus in samples taken from patients.